CHAPLIN AMYLOID FIBER FORMATION AND THE ROLE OF THE CHAPLINS IN THE AERIAL DEVELOPMENT OF STREPTOMYCES COELICOLOR - Capstick, David S. (My University, 2011)
The chaplin proteins are functional amyloids that are produced by filamentous Streptomyces bacteria. The chaplins are essential for the morphological development of S. coelicolor, and are important for altering the surface ultrastructure of aerial hyphae and spores. Although it is well established that the chaplins play an important role in S. coelicolor aerial development, there is still much that remains unknown regarding their activity; in particular, how each of the chaplins contribute to promoting aerial development, and the importance that chaplin amyloidogenesis has in this process.
Previous work has revealed that only three of the eight chaplins (ChpE, ChpC, and ChpH) are necessary for promoting aerial development, and that ChpH plays a significant role in this process. For this reason, ChpH was used as the ‘model chaplin’ to examine the primary sequence determinants governing chaplin amyloidogenesis, and to explore the relationship between ChpH amyloid fiber formation and ChpH-dependent aerial development. This analysis revealed that ChpH contains two amyloidogenic regions, at the N- and C-termini, both of which are necessary for promoting aerial development, while the N-terminal domain is dispensable for surface fiber assembly.
A separate study focused on the role of the short chaplin ChpE. One of the surprising findings of this work is that, unlike the other chaplins, ChpE is essential for maintaining cell viability. The relationship between ChpE cell surface localization and the presence of the long chaplins was also examined. This work showed that the long chaplins are not required for the surface attachment of ChpE (nor the other short chaplins), but do function to enhance the activity of the short chaplins in promoting aerial development, in addition to being necessary for the organization and assembly of surface fibers.
Keywords: Streptomyces development; surface ultrastructure; sporulation; functional amyloid; Molecular Biology; Molecular Biology